2008
DOI: 10.1016/j.jbiomech.2008.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic deformational loading does not counteract the catabolic effects of interleukin-1 in long-term culture of chondrocyte-seeded agarose constructs

Abstract: An interplay of mechanical and chemical factors is integral to cartilage maintenance and/or degeneration. Interleukin-1 (IL-1) is a pro-inflammatory cytokine that is present at elevated concentrations in osteoarthritic joints and initiates the rapid degradation of cartilage when cultured in vitro. Several short-term studies have suggested that applied dynamic deformational loading may have a protective effect against the catabolic actions of IL-1. In the current study we examine whether the long-term (42 days)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 49 publications
3
20
1
Order By: Relevance
“…37 Work in our laboratory has found that engineered bovine cartilage constructs with native properties can be protected from the deleterious effects of IL-1a by culture supplementation with dex, in a manner similar to native cartilage explants. [38][39][40] Additionally, preexposure to dex has been reported to prevent proteoglycan degradation and restore biosynthesis of cartilage explants exposed to TNF-a and mechanical injury. 40 Several in vivo studies have demonstrated the chondroprotective effects of dex as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Work in our laboratory has found that engineered bovine cartilage constructs with native properties can be protected from the deleterious effects of IL-1a by culture supplementation with dex, in a manner similar to native cartilage explants. [38][39][40] Additionally, preexposure to dex has been reported to prevent proteoglycan degradation and restore biosynthesis of cartilage explants exposed to TNF-a and mechanical injury. 40 Several in vivo studies have demonstrated the chondroprotective effects of dex as well.…”
Section: Introductionmentioning
confidence: 99%
“…38,39,56,57 As these factors can impact clinical success of cartilage tissue engineering strategies, we sought to develop a more clinically focused cartilage tissue engineering approach utilizing the FDAapproved steroid dex. An ideal therapy would retain the benefits of dex on engineered cartilage without the requirement for its exogenous supplementation, obviating the systemic 58 and joint level complications associated with clinical injections of steroids.…”
Section: Introductionmentioning
confidence: 99%
“…37,38 Delivery of nanoceria particles within the construct or through the culture medium did not protect the engineered cartilage from high concentrations of IL-1a (10 ng/mL). However, it should be noted that while the concentration of IL-1a used here (10 ng/ mL) is typical of in vitro studies, 6,7,39,40 it is two orders of magnitude greater than the measured in vivo concentrations of IL-1a and IL-1b for arthritic or arthritic-like conditions. 37,38 Based on our findings, we conditionally accept our hypothesis that the detrimental effects of IL-1a can be deactivated by interacting with nanoceria and is comparable with observations by previous studies that have used mammalian cell lines.…”
Section: Fig 5 Optical Images Of Individual Chondrocyte Cellsmentioning
confidence: 77%
“…The intermediate IL-1a concentration of 0.5 ng/ mL was selected to represent in vivo conditions, 37,38 whereas 10 ng/mL is known to be an effective concentration for inflammatory damage under in vitro conditions. 6,7,39,40 Cell viability was evaluated using live/dead cytotoxicity kit (Life Technologies) and examined using a confocal microscope (Olympus Fluoview-100, Center Valley, PA). Living cells were stained with calcein-AM, which fluoresces green, and dead cells were stained with ethidium homodimer-1, which fluoresces red.…”
Section: Experimental Designmentioning
confidence: 99%
“…We previously cultured juvenile bovine chondrocytes in 3D agarose hydrogels that achieved physiologic cartilage tissue properties (Bian et al, 2009;Lima et al, 2007;Lima et al, 2008;Mauck et al, 2003). Recently, the clinical potential of mesenchymal stem cells (MSCs) has motivated efforts toward their optimization for tissue engineering applications (Buxton et al, 2011;Gong et al, 2010;Huang et al, 2010;Lima et al, 2007;Moutos et al, 2010;Ronziere et al, 2010).…”
Section: Introductionmentioning
confidence: 99%